2011
DOI: 10.1111/j.1365-2265.2011.04135.x
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated ghrelin is associated with changes in insulin sensitivity and lipid profile during an exercise intervention

Abstract: Increase in UAG level was associated with improved insulin sensitivity via mechanisms independent of weight loss during an intensive, long-term exercise intervention in young healthy men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
1
21
1
3
Order By: Relevance
“…Of the 100 included studies, 46 included young male participants only with 18 (18% of total studies and 39.1% of young adult male only studies) [5254, 57, 58, 60, 61, 6473, 76] for physical inactivity, 14 (14% of total studies and 30.4% of young adult male only studies) for unsafe sexual behaviour [51, 80, 82, 8591, 94, 96–98], 4 (4% of total studies and 8.7% of young adult male only studies) for alcohol use [126129], 2 (2% of total studies and 4.3% of young adult male only studies) for unsafe vehicle driving [104, 105] 1 (1% of total studies and 2.2% of young adult male only studies) for tobacco smoking [110], 1 (1% of total studies and 2.2% of young adult male only studies) for poor diet [103], and 1 (1% of total studies and 2.2% of young adult male only studies) for tanning/sun exposure [115]. Also 5 (5% of total studies and 10.9% of young adult male only studies) of the studies with only young adult male participants targeted multiple risk behaviours [116, 119, 122, 124, 125].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 100 included studies, 46 included young male participants only with 18 (18% of total studies and 39.1% of young adult male only studies) [5254, 57, 58, 60, 61, 6473, 76] for physical inactivity, 14 (14% of total studies and 30.4% of young adult male only studies) for unsafe sexual behaviour [51, 80, 82, 8591, 94, 96–98], 4 (4% of total studies and 8.7% of young adult male only studies) for alcohol use [126129], 2 (2% of total studies and 4.3% of young adult male only studies) for unsafe vehicle driving [104, 105] 1 (1% of total studies and 2.2% of young adult male only studies) for tobacco smoking [110], 1 (1% of total studies and 2.2% of young adult male only studies) for poor diet [103], and 1 (1% of total studies and 2.2% of young adult male only studies) for tanning/sun exposure [115]. Also 5 (5% of total studies and 10.9% of young adult male only studies) of the studies with only young adult male participants targeted multiple risk behaviours [116, 119, 122, 124, 125].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining interventions were carried out in Europe (n = 18, 18%) [52, 53, 55, 56, 60, 61, 70, 81, 95, 98, 102, 104, 110, 116, 119, 127, 128, 148], Australasia (n = 8, 8%) [54, 65, 66, 105, 108, 120, 124, 149], Asia (n = 6, 6%) [64, 67, 71, 72, 107, 114], South America (n = 3, 3%) [69, 79, 83], Africa (n = 1, 1%) [76] and one intervention (1%) was implemented in multiple countries across two continents (USA, Ecuador, Peru and Brazil) [84]. The risk behaviours that were targeted in various intervention countries, separated by studies with young adult male participants only and studies with outcomes stratified by age/sex to include young adult males are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, GO-CoA-Tat did not suppress weight gain in ghrelin-deficient mice that lack both AG and DAG, suggesting that these animals are less responsive because of their DAG deficiency (24). Reports suggesting that high DAG levels might be linked to positive metabolic effects include a report by Cederberg et al (25). They found that 6 months of intensive exercise in 552 young men increased DAG levels, which was associated with decreased body weight and improved body composition.…”
Section: European Journal Of Endocrinologymentioning
confidence: 87%